Comparing ablation properties of NbC and NbC-25 mol.% ZrC coating on SiC-coated C/C composites. Issue 6 (15th April 2020) - He, Ruixiang; Li, Kezhi; Gu, Shengyue; Liu, Qian
Abstract: In this work, ablation properties of NbC and NbC-25 mol.% ZrC coating, deposited on SiC-coated C/C composites by supersonic atmospheric plasma spraying, were tested by an oxyacetylene torch. Results showed that, for NbC coating, an unexpected smooth liquid film mostly composed of niobium suboxides (such as NbO2 and NbO), rather than pure Nb2 O5, generated during ablation for 45 s. Mechanical erosion resulted from the molten SiO2, and the relatively low viscosity of the outer oxide layer owing to insufficiently high melting point of niobium suboxides were the key factors for the failure mechanism of NbC coating. While NbC–ZrC coating abated for 90 s has a 97.49 and 66.53% decrease of linear and mass ablation rate relative to NbC coating ablated for 45 s, since ZrO2 hindering the evaporation of SiO2 droplets, and more thermal-stable Nb–O–Zr liquid film endow (NbC–ZrC)/SiC/C/C composites with an outstanding anti-ablation property.